The Orthopaedic Management of Arthrogryposis Multiplex Congenita: Current Concept Review - van Bosse, Harold; Zlotolow, Dan (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Arthrogryposis multiplex congenita (AMC) is a term that describes at least 400 different conditions that result in a baby born with multiple joint contractures. The underlying similarity of these causative conditions is that the developing baby experiences fetal akinesia. The most common forms of AMC are Amyoplasia, or “classic arthrogryposis”, and the different kinds of distal arthrogryposis. Over the past two decades, the orthopaedic treatment of children with arthrogryposis multiplex congenita has steadily evolved steadily, with a better appreciation of the functional potential of persons with arthrogryposis. The development of newer procedures specific for the arthrogrypotic deformities have improved surgical treatment, and outcomes studies that provide understanding of the overall capabilities of adults with arthrogryposis continue to help determine which treatments were the most beneficial. The outcome studies indicate that most adults with arthrogryposis are ambulatory, but less than half are fully independent in self-care, most are limited by upper extremity dysfunction. Pain in adulthood, both chronic and episodic, is frequent, particularly of the foot and back, limiting ambulation and standing. To improve independence, upper extremity treatments have advanced to improve elbow motion, and wrist and thumb positioning. In the lower extremities, attempts to improve the ambulatory ability and decrease future pain include correction of hip and knee contractures, and emphasizing casting treatments of foot deformities. Pediatric patients with arthrogryposis require a careful evaluation, with both a physical examination and an assessment of needs to direct their treatment. Further outcomes studies are needed to continue to refine procedures and define the appropriate candidates.